Introduction of strategic management in public health institutions - V. V. Portnykh (Вестник университета, 2019)
The concept of strategic management has been substantiated. The key tasks of strategic management of the state medical institution have been defined. The urgency of implementation of strategic management in public medical institutions has been proved. The structure of the strategic management process in the state clinical hospital has been substantiated. The main stages of the project of implementation of strategic management in the state clinical hospital have been defined, described and illustrated: setting the system of main goals, development of the strategic map, defi tion of indicators and target values of strategic objectives, development of operational plans for the implementation of strategic objectives. The tasks and practical activities of the strategic Committee as a body managing the development of medical institutions have been described.